RARE-19. CHEMOTHERAPY FOR SPINAL GLIOMAS IN ADULTS: A RETROSPECTIVE STUDY. (5th November 2018) - Gramatzki, Dorothee; Felsberg, Jörg; Baehr, Oliver; Hentschel, Bettina; Westphal, Manfred; Schackert, Gabriele; Tonn, Jörg-Christian; Herrlinger, Ulrich; Steinbach, Joachim; Reifenberger, Guido; Roth, Patrick; Weller, Michael
Abstract: BACKGROUND: Chemotherapy is a treatment option in patients diagnosed with anaplastic gliomas or glioblastomas of the spinal cord, or with recurrent lower World Health Organization (WHO) grade spinal gliomas that are no longer amenable to local treatment. The low incidence of spinal cord gliomas, particularly in adults, limits the ability to perform clinical trials. The role of chemotherapy in these tumors has remained unclear. METHODS: We performed a retrospective study of 21 patients diagnosed with spinal gliomas who were treated with chemotherapy at any time during the disease course. Benefit from chemotherapy was estimated by applying Response assessment in neuro-oncology criteria. RESULTS: Patients were diagnosed with myxopapillary ependymoma (N=3), anaplastic ependymoma (N=5), pilocytic astrocytoma (N=4), astrocytoma (N=2), anaplastic astrocytoma (N=3) or glioblastoma (N=4). Median follow-up from start of chemotherapy was 59 months. Nine of 12 patients with known MGMT status had tumors with MGMT promoter methylation. Eight patients had chemotherapy as part of first-line treatment: patients with glioblastoma received temozolomide (TMZ) (N=3) or vincristine/etoposide/cisplatin/ifosfamide (N=1); patients with astrocytoma (N=1), with anaplastic astrocytoma (N=2) and with anaplastic ependymoma (N=1) received TMZ. All other patients had chemotherapy at progression which included alkylating agents (N=9), carboplatin-based chemotherapy (N=2), hydroxycarbamid (N=1), or ifosfamide/etoposide/doxorubicin (N=1). Response rates were as follows: myxopapillary ependymoma 3 stable diseases; anaplastic ependymoma 1 partial response (N=2 data missing); pilocytic astrocytoma 1 stable disease; astrocytoma 1 stable disease, anaplastic astrocytoma 2 stable diseases (N=2 data missing); glioblastoma 1 complete response and 1 stable disease. There was no indication for a favorable prognostic role of MGMT promoter methylation. CONCLUSIONS: Spinal cord gliomas represent a heterogeneous group of tumors. Survival outcomes in response to chemotherapy in adult spinal glioma patients vary substantially, but individual patients appear to derive benefit from chemotherapy.